1995
DOI: 10.1128/aem.61.1.245-251.1995
|View full text |Cite
|
Sign up to set email alerts
|

Application of ribotyping for differentiating Vibrio cholerae non-O1 isolated from shrimp farms in Thailand

Abstract: A collection of 143 Vibrio cholerae non-O1 strains isolated from shrimp farms in Thailand were characterized and grouped by ribotyping. Sixty-four ribotypes were distinguished following digestion of chromosomal DNA with the restriction enzyme BglI, and the reproducibility of the method was 100%. There was no correlation between specific ribotype distributions and the locations of the shrimp farms. Ribotype similarity was examined by cluster analysis, and two main groups with 10 and 54 ribotypes, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
2
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 44 publications
4
28
2
2
Order By: Relevance
“…Repeated studies of all strains showed no variation in ribotype patterns, although differences in band intensity and the degree of background were observed for a few strains. A high degree of reproducibility of the BglI ribotypes of V. cholerae has been reported previously (6,22). The ribotype patterns produced with the restriction enzyme HindIII were identical for the 19 strains studied (data not shown).…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Repeated studies of all strains showed no variation in ribotype patterns, although differences in band intensity and the degree of background were observed for a few strains. A high degree of reproducibility of the BglI ribotypes of V. cholerae has been reported previously (6,22). The ribotype patterns produced with the restriction enzyme HindIII were identical for the 19 strains studied (data not shown).…”
Section: Resultssupporting
confidence: 60%
“…The ribotype patterns produced with the restriction enzyme HindIII were identical for the 19 strains studied (data not shown). Thus, our study provides further evidence that BglI is suitable for use in ribotyping V. cholerae strains (5)(6)(7)22).…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Vibrio alginolyticus (George et al 2005); Vibrio parahaemolyticus and V. alginolyticus (Sudheesh et al 2002); V. parahaemolyticus (Maluping et al 2005). Dalsgaard et al (1995) applied ribotyping to differentiate V. cholerae non-O1 isolated from shrimp farms in Thailand. The genetic diversity of V. cholerae was determined by multilocus enzyme electrophoresis (Desmarchelier et al 1988;Chen et al 1991), ribotyping (Koblavi et al 1990;Karaolis et al 1994), pulsed-field gel electrophoresis (Cameron et al 1994) and amplified fragment length polymorphism fingerprinting (Jiang et al 2000).…”
Section: Introductionmentioning
confidence: 99%